Premature Mortality Due to Hodgkin Lymphoma, Non-Hodgkin Lymphoma, Multiple Myeloma, and Leukemia in Canada: A Nationwide Analysis From 1980 to 2015. Issue 1 (24th July 2020) - Pham, Truong-Minh; Shen-Tu, Grace; Nguyen, Khanh Hoa; Lu, Shuang; Dover, Douglas C; Duggan, Peter; Shack, Lorraine; Cheung, Winson Y
Abstract: Recently, we introduced a novel measure of "average life span shortened" (ALSS) to improve comparability of premature mortality over time. In this study, we applied this novel measure to examine trends in premature mortality caused by hematological cancers in Canada from 1980 to 2015. Mortality data for Hodgkin lymphoma, non-Hodgkin lymphoma, multiple myeloma, and leukemia were obtained from the World Health Organization mortality database. Years of life lost was calculated according to Canadian life tables. ALSS was defined as the ratio between years of life lost and expected life span. Over the study period, age-standardized rates of mortality decreased for all types of hematological cancers. Our new ALSS measure showed favorable trends in premature mortality for all types of hematological cancers among both sexes. For instance, men with non-Hodgkin lymphoma lost an average of 23.7% of their life span in 1980 versus 16.1% in 2015, while women with non-Hodgkin lymphoma lost an average of 21.7% of their life span in 1980 versus 15.5% in 2015. Results from this study showed that patients with hematological cancers experienced prolonged survival over a 35-year period although the magnitude of these life span gains varied by types of hematological cancers.